2011
DOI: 10.1007/s11426-011-4401-0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct phase transitions and dielectric anomalies in two 4-methylanilinium salts

Abstract: were investigated with variable-temperature X-ray single-crystal structure analysis and thermal studies. Both 1 and 2 undergo first-order phase transitions and exhibit distinct dielectric anomalies at 385 and 247 K, respectively. organic-inorganic hybrid compounds, dielectricity, phase transition, crystal structure, switchable molecular dielectrics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It indicates the motional changes, especially the pyridinium cation, is largely restricted. Otherwise, there should be a large dielectric change (e.g., Δε′ ≈ 10), as seen in other dynamic molecular crystals. Another striking feature of the ε′ is a gradual increase at temperatures below the T c . Such a fluctuation may be ascribed to a pretransitional effect because of molecular motions such as reorientation …”
Section: Resultsmentioning
confidence: 96%
“…It indicates the motional changes, especially the pyridinium cation, is largely restricted. Otherwise, there should be a large dielectric change (e.g., Δε′ ≈ 10), as seen in other dynamic molecular crystals. Another striking feature of the ε′ is a gradual increase at temperatures below the T c . Such a fluctuation may be ascribed to a pretransitional effect because of molecular motions such as reorientation …”
Section: Resultsmentioning
confidence: 96%
“…This pair of sharp peak‐like dielectric anomalies reveals a reversible structural phase transition in 1 at about 230 K with a 10 K hysteresis. Increases of the ϵ ′ values at the peaks are about 10 %, indicating the phase transition has a small structural change 28,29…”
Section: Resultsmentioning
confidence: 99%
“…Molecular switchable dielectric materials, which undergo transitions between high and low dielectric states at the phase transition temperature, have attracted great attention due to their potential applications in data communication, signal processing, rewritable optical data storage, and varactors. At present, an efficient method to obtain switchable and tunable molecular dielectric materials is to construct molecular systems with molecular motions, including order–disorder transformations and rotational and orientational motions. For instance, Zhang et al reported the amphidynamic crystal [(CH 3 ) 2 NH 2 ] 2 [KCo­(CN) 6 ] exhibiting a tunable and switchable dielectric constant, where the ordered–disordered transformation of the dimethylammonium cation relates to the main factor for the phase transition . In addition, in the new perovskite-like coordination polymer [(CH 3 ) 2 NH 2 ]­[Cd­(N 3 ) 3 ], varied modes of motions of the [(CH 3 ) 2 NH 2 ] + guest accompanied by a synergistic deformation of the [Cd­(N 3 ) 3 ] – framework are responsible for the ferroelastic phase transition .…”
Section: Introductionmentioning
confidence: 99%